Asian australasian society of stereotactic and functional neurosurgery - Idris, Zamzuri (Universiti Sains Malaysia, 2012)
Stereotactic Brain Surgery: from simple lesional biopsy to deep brain stimulation in dystonia and Tourette syndrome